Ultrasound assessment of the respiratory system using diaphragm motion-volume indices - Boussuges, Alain; Chaumet, Guillaume; Boussuges, Martin; Menard, Amelie; Delliaux, Stephane; Brégeon, Fabienne (Frontiers in Medicine, 2023)
Background Although previous studies have determined limit values of normality for diaphragm excursion and thickening, it would be beneficial to determine the normal diaphragm motion-to-inspired volume ratio that integrates the activity of the diaphragm and the quality of the respiratory system. Methods To determine the normal values of selected ultrasound diaphragm motion-volume indices, subjects with normal pulmonary function testing were recruited. Ultrasound examination recorded diaphragm excursion on both sides during quiet breathing and deep inspiration. Diaphragm thickness was also measured. The inspired volumes of the corresponding cycles were systematically recorded using a spirometer. The indices were calculated using the ratio excursion, or percentage of thickening, divided by the corresponding breathing volume. From this corhort, normal values and limit values for normality were determined. These measurements were compared to those performed on the healthy side in patients with hemidiaphragm paralysis because an increase in hemidiaphragm activity has been previously demonstated in such circumstances. Results A total of 122 subjects (51 women, 71 men) with normal pulmonary function were included in the study. Statistical analysis revealed that the ratio of excursion, or percentage of thickening, to inspired volume ratio significantly differed between males and females. When the above-mentioned indices using excursion were normalized by body weight, no gender differences were found. The indices differed between normal respiratory function subjects and patients with hemidiaphragm paralysis (27 women, 41 men). On the paralyzed side, the average ratio of the excursion divided by the inspired volume was zero. On the healthy side, the indices using the excursion and the percentage of thickening during quiet breathing or deep inspiration were significantly increased comparedto patients with normal lung function. According to the logistic regression analysis, the most relevant indice appeared to be the ratio of the excursion measured during quiet breathing to the inspired volume. Conclusion The normal values of the diaphragm motion-volume indices could be useful to estimate the performance of the respiratory system. Proposed indices appear suitable in a context of hyperactivity.